Design and Build of a Multifunctional Portable Fertilizer - Zunanik Mufidah; Sabar Sabar; Bagus Hermanto; Agung Cahyono; Adi Mas Sulton; Intan Avionita; Sujatmiko Sujatmiko; Sri Mursidah (Fakultas Teknologi Industri Pertanian, 2023)
Pangestu Farmer Group is a farming group in Pandanrejo Village, Batu Regency, that has high-quality sweet corn as a strategic asset with often fluctuating yields. Consequently, the market demand cannot be met. The main problem of fluctuations in corn yields is due to improper fertilization methods. Applying liquid fertilizer during the rainy season can result in nutrients being washed away by rainwater, but when granular fertilization is used, this results in increased costs and labour. A solution is needed to solve this problem so that the fertilization process is correct, and the timing of fertilization and labour costs can be reduced. Therefore, a portable fertilizing technology based on spring valves is needed. The goal is to develop and manufacture a valve spring-based portable fertilizer that can increase the effectiveness and efficiency of the fertilization process. The comparison of type 1 and type 2 fertilizers lies in the raw material used. Commercially available hand sprayer for comparison in design. Ergonomic analyses are also considered in the design of the fertilizer, both in terms of user safety and comfort. The method in this study is to design tools with power and ergonomic calculations, manufacture tools at Sahabat Teknik Workshop, and conduct tests at Brawijaya University's Agricultural Power and Machinery Laboratory. The test results for portable fertilizer types 1 and 2 show great advantages, namely, increase in working capacity 20 times to 1.2 ha/hour, reduce the number of workers from 7 people/ha to 5 people/ha, reduce operating time, reduce labour costs and increase farmers' income by up to 57, 72%/year.